2018
DOI: 10.1063/1.5018851
|View full text |Cite
|
Sign up to set email alerts
|

Annealing-time and annealing-temperature dependencies of the size of Ni-Mn-In shell-ferromagnetic nano-precipitates by Scherrer analysis

Abstract: Shell-ferromagnetic effects are observed in Ni-Mn-based off-stoichiometric Heuslers decomposed into ferromagnetic precipitates embedded in an antiferromagnetic matrix when the surface-to-volume ratio of the precipitates are sufficiently large. However, since the size of the precipitates have until now not been determined, it is not known which ratios are involved. Here we carry out a Scherrer analysis on decomposed specimens to determine the precipitate-size as a function of decomposition temperature and time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
3
17
1
Order By: Relevance
“…The present SANS data reveal no characteristic signature indicative of such presumably small precipitates, which might indicate that their size is too small and their volume fraction is too low to give rise to a corresponding feature in the observed q region. This is consistent with our synchrotron x-ray data analysis and with the results reported in [5], where precipitate sizes of the order of 3-5 nm were found for samples of similar annealing conditions.…”
Section: Unpolarized Sans Datasupporting
confidence: 93%
See 3 more Smart Citations
“…The present SANS data reveal no characteristic signature indicative of such presumably small precipitates, which might indicate that their size is too small and their volume fraction is too low to give rise to a corresponding feature in the observed q region. This is consistent with our synchrotron x-ray data analysis and with the results reported in [5], where precipitate sizes of the order of 3-5 nm were found for samples of similar annealing conditions.…”
Section: Unpolarized Sans Datasupporting
confidence: 93%
“…The histograms in Fig. 2(c suggest that the particle statistics have improved for the 700 K sample; that is, the vertical lines are more homogeneous, implying that the grain-size distribution has become less disperse after the heat treatment (in accordance with [5]). The presence of large crystals [large and intense spots in Fig.…”
Section: B Synchrotron X-ray Diffractionmentioning
confidence: 60%
See 2 more Smart Citations
“…It has been reported that the compound decomposes into FM nanoprecipitates embedded in a Ni 50 Mn 50 AF matrix at room temperature. Additionally, the negative shift of the magnetization in the Ni-Mn-In shell FM nano-precipitates has been attributed to the occurrence of the magnetic proximity effect, whereby the interfacial spins align along the field applied during segregation [31]. The spins at the interface with the NiMn matrix align with the annealing field during their growth and become strongly pinned in the field direction during annealing, forming the so-called shell ferromagnet.…”
Section: Magnetic Measurementsmentioning
confidence: 99%